2021
DOI: 10.3390/cells10112934
|View full text |Cite
|
Sign up to set email alerts
|

Decoupled Glucose and Lipid Metabolic Recovery after Viral Clearance in Direct-Acting Antiviral-Treated HCV Patients: A 3-Year Prospective Cohort Study

Abstract: Background/Aim: The recovery pattern of hepatitis C virus (HCV)-associated metabolic alteration after sustained virological response (SVR) following direct-acting antivirals (DAAs) remains elusive. Methods: A prospective cohort study of chronic HCV-infected (CHC) patients (n = 415) receiving DAAs (n = 365) was conducted. Metabolic profiles were examined in SVR patients (n = 360) every 3–6 months after therapy and compared with those of sex- and age-matched controls (n = 470). Results: At baseline, of 415, 168 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…On the other hand, a low fibrosis stage was associated with a reduction in HDL 61 . The study of Lee et al 91 . showed that patients with an increase in BMI and HOMA‐IR after SVR experienced a reduction in HDL 3 years after therapy.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…On the other hand, a low fibrosis stage was associated with a reduction in HDL 61 . The study of Lee et al 91 . showed that patients with an increase in BMI and HOMA‐IR after SVR experienced a reduction in HDL 3 years after therapy.…”
Section: Resultsmentioning
confidence: 98%
“…All studies observed a worsening in TC and LDL after viral eradication by DAAs. Concerning HDL, 17 studies did not show a significant change after SVR, 20 studies observed an increase in HDL after SVR, especially in female patients with metabolic syndrome, 22,45,64,72,95 but not during the treatment when HDL declined, 13,91,96 and only 2 studies revealed a reduction in HDL 61,91 . Finally, 19 studies did not show significant changes in TGs after viral eradication, 13,22,26,40,45,46,53,60,73,74,97–103 in 16 TGs worsened, 12,16,28,36,37,39,52,58,61,64,68,72,91,92,104,105 and in 9 studies TGs decreased after SVR 38,43,54–56,69,79,106,107 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[35] Therefore, IR is an important therapeutic target in patients at any stage of chronic liver disease. [36]…”
Section: Discussionmentioning
confidence: 99%
“…[35] Therefore, IR is an important therapeutic target in patients at any stage of chronic liver disease. [36] As a result of impaired liver function, HD usually exhibits specific clinical characteristics and is closely linked to hypoglycemic episodes, but has a less association with risk factors such as age, body mass index and a family history of diabetes. This is due to the fact that chronic liver illness, rather than a genetic predisposition, caused the diabetic state.…”
Section: Discussionmentioning
confidence: 99%